The effect of lime addition on weathering resistance and mechanical strength of gypsum plasters and renders. (May 2023) - Elert, Kerstin; Alabarce Alaminos, Ruben; Benavides-Reyes, Cristina; Burgos-Ruiz, Miguel
Abstract: Despite historical evidence revealing the extensive use of gypsum-lime plasters and renders for interior, exterior and structural applications in many parts of the world, systematic studies of the effect of varying amounts of lime on the properties of these materials are rare. Here we studied the influence of lime addition (5–95 wt% quicklime) on porosity, compressive and flexural strength, surface hardness, water vapor permeability and weathering resistance of gypsum-lime plasters in relation to their mineralogical composition, phase distribution, and textural characteristics. Results showed that even small lime additions resulted in reduced strength, but compatible conservation materials can be easily designed to match the properties of original historic plasters and renders, which are normally debilitated through deterioration. Moreover, lime additions significantly improved weathering resistance, thus enabling a wider use (including exterior applications) of gypsum-lime plasters, which could replace currently used building materials with larger carbon footprint in new constructions.